Capturing Parental Mentalization: A Thematic Analysis of Expert Perspectives in Elements Required for Valid Measures. (3rd April 2021) - Law, Abigail R. M.; Thackeray, Lisa; Morris, Emma; Sleed, Michelle
ABSTRACT: Parental Mentalization (PM) refers to parents' capacity to understand internal experiences of their children. It is linked with the development of children, as deficiencies in PM can lead to adverse life outcomes. PM measures assess the quality of parental mentalizing capacities, which may then inform intervention and research. However, current measures are limited by complexity of use and sensitivity to assessing the multiple features of mentalizing. Hence, understanding the essential elements required in PM measures is needed to capture PM in ways which are ecologically valid while also being practical to administer in routine practice. This current study aimed to provide a qualitative understanding of how PM may be best captured. Specifically, it aimed to identify essential elements necessary in the development of accurate PM measures for use in clinical and research settings. The study reports data from semi-structured interviews with five leading experts in PM. Interviews were analyzed using thematic analysis. Three themes were identified: "Capturing the breadth and depth of multiple dimensions, " "Capturing natural interactions between parent and child, " and "Parent profiling." This study highlights the essential elements which should be considered when choosing or developing PM measures. Clinical implications and further research for measure development are discussed.